Conducive conditions for curriculum practice in teaching accounting at a rural school in the KwaZulu-Natal - Walusa Ajuma; Molaodi Tshelane (International Journal of Studies in Inclusive Education)
The education landscape constantly evolves and brings new challenges and opportunities in teaching practices, particularly in specialised subjects such as accounting. The curriculum's adequacy and delivery significantly influence learners' preparedness for professional pathways and academic advancements. This paper presents a theoretical overview of the conditions conducive to practical curriculum practice in accounting instruction. Building on a synthesis of educational theories and empirical studies, we posit that a multidimensional approach incorporating pedagogical, contextual, technological, and evaluative components is necessary to align accounting education with the demands of the contemporary business environment. In recent years, discourse on teachers’ content knowledge, pedagogy knowledge, and pedagogical content knowledge and their influence on learners’ learning outcomes has garnered increasing attention from various stakeholders in the education sector. The theoretical framework we propose aims to support teachers and curriculum developers in fostering educational experiences that enhance learners' engagement and understanding and in applying accounting principles in a multifaceted world. Key to this framework is the integration of technology in pedagogy, the responsiveness of curriculum content to market needs, the adoption of diverse and inclusive teaching methods, and a continuous feedback mechanism to refine teaching strategies. This overview serves as a guide for promising practices and a catalyst for further research on optimising accounting education in a rapidly changing economic landscape.